Analysis of Remifentanil with Liquid Chromatography-Tandem Mass Spectrometry and an Extensive Stability Investigation in EDTA Whole Blood and Acidified EDTA Plasma. (June 2015) - Koster, Remco A.; Vereecke, Hugo E. M.; Greijdanus, Ben; Touw, Daan J.; Struys, Michel M. R. F.; Alffenaar, Jan Willem C.
Abstract : BACKGROUND: Remifentanil is a μ-opioid receptor agonist that was developed as a synthetic opioid for use in anesthesia and intensive care medicine. Remifentanil is rapidly metabolized in both blood and tissues, which results in a very short duration of action. Even after blood sampling, remifentanil is unstable in whole blood and plasma through endogenous esterases and chemical hydrolysis. The instability of remifentanil in these matrices makes sample collection and processing a critical phase in the bioanalysis of remifentanil. METHODS: We have developed a fast and simple sample preparation method using protein precipitation followed by liquid chromatography-tandem mass spectrometry analysis. To improve the stability of remifentanil, citric acid, ascorbic acid, and formic acid were investigated for acidification of EDTA plasma. The stability of remifentanil was investigated in stock solution, EDTA whole blood, EDTA plasma, and acidified EDTA plasma at ambient temperature, 4°C, 0°C, and at −20°C. RESULTS: The analytical method was fully validated based on the Food and Drug Administration guidelines for bioanalytical method validation with a large linear range of 0.20 to 250 ng/mL remifentanil in EDTA plasma acidified with formic acid. The stability results of remifentanil in EDTA tubes, containing whole blood placed in ice water, showed a decrease of approximately 2% in 2 hours. EDTA plasma acidified with citric acid, formic acid, and ascorbic acid showed 0.5%, 4.2%, and 7.2% remifentanil degradation, respectively, after 19 hours at ambient temperature. Formic acid was chosen because of its volatility and thus liquid chromatography-tandem mass spectrometry compatibility. The use of formic acid added to EDTA plasma improved the stability of remifentanil, which was stable for 2 days at ambient temperature, 14 days at 4°C, and 103 days at −20°C. CONCLUSIONS: The analytical method we developed uses a simple protein precipitation and maximal throughput by a 2-point calibration curve and short run times of 2.6 minutes. Best sample stability is obtained by placing tubes containing EDTA whole blood in ice water directly after sampling, followed by centrifugation and transfer of the EDTA plasma to tubes with formic acid. The stability of remifentanil in EDTA plasma was significantly improved by the addition of 1.5 μL formic acid per milliliter of EDTA plasma. This analytical method and sample pretreatment are suitable for remifentanil pharmacokinetic studies. Abstract : Published ahead of print February 16, 2015